A spatially‐explicit assessment of the fish population response to flow management in a heterogeneous landscape. Issue 5 (25th May 2016) - Guénard, Guillaume; Lanthier, Gabriel; Harvey‐Lavoie, Simonne; Macnaughton, Camille J.; Senay, Caroline; Lapointe, Michel; Legendre, Pierre; Boisclair, Daniel
Abstract: Ecological processes are structured in space and there are important benefits in incorporating spatial information for the analysis of data sets obtained from field studies. Assessing the effect of different flow management practices on river ecosystems is an example where such an exercise is highly relevant. Human activities such as hydroelectric power production are known to modify the temporal variability in river flow. Flow management strategies may have a direct influence on fishes and may trigger complex cascades of interactions involving different features of the river ecosystem. In this study, we performed an assessment of the effect of different flow management practices on fish count density (no. fish/m2 ), biomass density (g/m 2 ), and species richness. Data were collected in 941 sites located along 28 Canadian rivers. These rivers were either naturally flowing or had altered flows from one of three flow management strategies: run of the river dams, storage with gradual release, or storage with peak release. Each site (300 m 2 ) was surveyed using paired snorkeling and electrofishing techniques; environmental variables (water depth and velocity, and substrate composition) were also measured. The study spanned a broad geographic range (3497 km, geodesic distance) and involved repeated local observations (16–50 sites/river), and was therefore inherently spatially organized. We used spatial modeling to obtain a baseline to estimate the effect of flow management strategies on fishes. Our results indicate that rivers downstream of flow peaking storage dams have, by far, the lowest fish densities (count and biomass) and species richness, whereas those downstream of gradual release storage dams had higher fish biomass density than the unregulated rivers.